Competing Notions of Law in American Civil Religion - D. H. Davis (Law Text Culture, 2000)
The presence of a civil religion in America is now widely accepted. While its specific content is still debated, most agree that civil religion is essentially about those public rituals and myths that express for most Americans the nexus of the political order to the divine reality. According to Robert Bellah, who stimulated much of the discussion about civil religion with his seminal essay in 1967, civil religion in America is "an understanding of the American experience in the light of ultimate and universal reality."